Respuesta :
Answer:
[tex]ln\hspace{1mm} e^3=3[/tex], [tex]ln\hspace{1mm} e^{2y}=2y[/tex]
Step-by-step explanation:
We know that [tex]ln \hspace{1mm} e =log_e e= 1[/tex] and according to power rule:
[tex]ln(x^y) = y ln(x)[/tex]
Thus,
[tex]ln\hspace{1mm}e^3=3 ln\hspace{1mm} e =3 [/tex]
[tex] ln\hspace{1mm}e^{2y}=2y ln\hspace{1mm} e = 2y[/tex]
The expressions of log equations can modify by using the properties of the log.
The simplified expressions are [tex]In\;e^3 = 3 In\;e[/tex] and [tex]In\;e^{2y} = 2y In\;e[/tex].
How do you simplify the logarithm expression?
The four basic properties of Logs are given below.
[tex]log_b (xy) = log_b x + log_b y.[/tex]
[tex]log_b (\dfrac {x}{y}) = log_b x - log_b y.[/tex]
[tex]log_b (x^n) = n log_b x.[/tex]
[tex]log_b x = \dfrac {log_a x}{ log_a b}[/tex]
The given expression is [tex]ln \;e^3[/tex] and [tex]In\;e^{2y}[/tex].
The above expressions of the logarithm can be solved by using the third property of log.
Part A:
The expression of the logarithm is [tex]In\;e^3[/tex].
This can be written as using one of the properties of the log.
[tex]In\;e^3 = 3 In\;e[/tex]
Part B:
The expression of the logarithm is [tex]In\;e^{2y}[/tex].
This can be written as using one of the properties of the log.
[tex]In\;e^{2y} = 2y In\;e[/tex]
Hence we can conclude that the expressions of log equations can modify by using the properties of the log.
The simplified expressions are [tex]In\;e^3 = 3 In\;e[/tex] and [tex]In\;e^{2y} = 2y In\;e[/tex].
To know more about the logarithm, follow the link given below.
https://brainly.com/question/7302008.